Investigating Nuclear War Dangers under Spatial Grasp Paradigm - Sapaty, P.S. (Математичні машини і системи, 2019)
The paper describes applicability of the developed Spatial Grasp Technology (SGT) for describing patterns of international relations that can hint on probability of nuclear wars, while applying them worldwide in parallel and distributed mode. These recursive patterns in high-level language can be regularly launched and spatially matched from any world points, allowing us to investigate world security more efficiently than in a traditional centralised way. SGT is ideologically based on quite different, holistic, world vision directly as integral shapes and patterns rather than traditional parts-to-whole models. Its key element is high-level recursive Spatial Grasp Language (SGL) which can express distributed spaces and operations in them in a way understandable to both manned and unmanned components.